2014
DOI: 10.21825/vdt.v83i3.16651
|View full text |Cite
|
Sign up to set email alerts
|

Chronisch progressief lymfoedeem bij het Belgisch trekpaard in België: klinische fenotypering, prevalentie en analyse van risicofactoren

Abstract: Chronic progressive lymphedema (CPL) is a well-known problem in the Belgian draft horse. However, tools for clinical diagnosis have not been standardized. Therefore, the exact disease prevalence and the possible CPL risk factors have not been investigated in the Belgian breed yet. The aim of the present study was to assess a uniform CPL clinical examination method to increase diagnostic objectivity as well as to determine the occurrence and severity of lesions. Using univariate and stepwise multivariable logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(28 citation statements)
references
References 9 publications
2
23
1
Order By: Relevance
“…In 912 draught horses, including all different German draught horse breeds, sex and linear regression on age were significant for the prevalence of CPL and number of limbs affected with CPL [ 1 ]. Both studies with 431 and 980 records of Belgian draught horses confirmed the significant effects of age and sex by age on CPL severity [ 2 , 24 ]. Stallions tended to develop CPL-lesions quicker than mares [ 24 ].…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…In 912 draught horses, including all different German draught horse breeds, sex and linear regression on age were significant for the prevalence of CPL and number of limbs affected with CPL [ 1 ]. Both studies with 431 and 980 records of Belgian draught horses confirmed the significant effects of age and sex by age on CPL severity [ 2 , 24 ]. Stallions tended to develop CPL-lesions quicker than mares [ 24 ].…”
Section: Introductionmentioning
confidence: 84%
“…Chronic progressive lymphedema (CPL) is a common disease in draught horses [ 1 , 2 , 3 , 4 , 5 ]. The first reports of CPL in draught horses date from the early 1900s and indicate a considerable number of German draught horses were affected [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations